The Fate of Two Unstoppable Trains After Arriving Destination: Replisome Disassembly During DNA Replication Termination - Xia, Yisui (Frontiers in Cell and Developmental Biology, 2021)
In eukaryotes, the perfect duplication of the chromosomes is executed by a dynamic molecular machine called the replisome. As a key step to finishing DNA replication, replisome disassembly is triggered by ubiquitylation of the MCM7 subunit of the helicase complex CMG. Afterwards, the CDC48/p97 “unfoldase” is recruited to the ubiquitylated helicase to unfold MCM7 and disassemble the replisome. Here we summarise recently discovered mechanisms of replisome disassembly that are likely to be broadly conserved in eukaryotes. We also discuss two crucial questions that remain to be explored further in the future. Firstly, how is CMG ubiquitylation repressed by the replication fork throughout elongation? Secondly, what is the biological significance of replisome disassembly and what are the consequences of failing to ubiquitylate and disassemble the CMG helicase?